The characteristics of nutrient distribution and influencing factors in the Chukchi Plateau and adjacent waters - Ni, Zhixin; Zhang, Han; Zhang, Minxia; Li, Tuanjie; Li, Shengyong; Chen, Xin; Zhang, Ling; Gao, Yuan; Chen, Changshu; Wang, Zhongyuan; Deng, Wei; Zhang, Hai zhou (Frontiers in Marine Science, 2024)
The Arctic is one of the regions under the most dramatic climate change. Global warming has led to elevated freshwater inflow into the western Arctic Ocean and significantly altered the structure and the biogeochemical cycling of nutrients. In this work, inorganic dissolved nutrients in the Chukchi Plateau (CP) and adjacent regions were investigated to further understand their characteristics and influencing factors. Results showed that relatively high nutrient concentrations occurred in the water masses with salinity >32 psu, especially there was a nutrient-rich layer influenced by Winter Pacific Water in the water column (15.10±1.96, 2.23±0.26, and 23.46±6.64 µmol/L for DIN, PO4 3-and Si(OH)4, respectively). Contrarily, lower concentrations occurred in the mixing water of the upper layer (1.76±1.04, 1.15±0.16 and 3.76±2.29 µmol/L for DIN, PO4 3-and Si(OH)4, respectively) with a low DIN/P ratio (1.44±0.59), suggesting DIN has become the potentially biological limiting factor despite limited supplement from freshwater inputs. Furthermore, the freshening and deepening of the upper layer driven by the Beaufort Gyre has hindered the nutrient transport from underlying layer into the upper layer. A maximum chla was found at 36-75 m depth, and the phytoplankton biomass decreased from the western to the eastern CP, accompanied by a decreased contribution of micro-sized chla but an increased contribution of small-sized chla (74.0±0.1%). The resource use efficiency (RUE) of phytoplankton was estimated as (2.3±3.1)×10 -3 , (0.5±0.7)×10 -3 and (3.2±4.6)×10 -3 for P, Si and DIN, respectively, which were primarily influenced by the physicochemical parameter of water, and was also largely regulated by the size structure of phytoplankton.